Mechanical avalanches promoted by magnetoelastic coupling in magnetic metallic glasses. (29th October 2018) - Herrero-Gómez, Carlos; Samwer, Konrad
Abstract: The effect of magnetoelastic coupling on the mechanical behavior of magnetic metallic glasses is studied by superposing a magnetic field to the mechanical load during deformation experiments. The mechanical response is studied from the point of view of the global behavior, characterized by the Young's modulus, and from the perspective of the avalanches, estimated from the intermittency of the deformation signal. The influence of several intensities and orientations of magnetic field is analyzed in two amorphous alloys with different magnetostriction. For the highly magnetostrictive alloy, the decrease of the macroscopic Young's modulus under certain magnetic fields is accompanied by the promotion of mechanical avalanches, a fact that suggests that in this case the magnetoelastic coupling involves some extent of non-linear addition of the magnetic and mechanical energies.